Enhanced primary mental healthcare for Indigenous Australians: service implementation strategies and perspectives of providers - Lennart Reifels; Angela Nicholas; Justine Fletcher; Bridget Bassilios; Kylie King; Shaun Ewen; Jane Pirkis (BMC, 2018)
Abstract Background Improving access to culturally appropriate mental healthcare has been recognised as a key strategy to address the often greater burden of mental health issues experienced by Indigenous populations. We present data from the evaluation of a national attempt at improving access to culturally appropriate mental healthcare for Indigenous Australians through a mainstream primary mental healthcare program, the Access to Allied Psychological Services program, whilst specifically focusing on the implementation strategies and perspectives of service providers. Methods We conducted semi-structured interviews with 31 service providers (primary care agency staff, referrers, and mental health professionals) that were analysed thematically and descriptively. Results Agency-level implementation strategies to enhance service access and cultural appropriateness included: the conduct of local service needs assessments; Indigenous stakeholder consultation and partnership development; establishment of clinical governance frameworks; workforce recruitment, clinical/cultural training and supervision; stakeholder and referrer education; and service co-location at Indigenous health organisations. Dedicated provider-level strategies to ensure the cultural appropriateness of services were primarily aimed at the context and process of delivery (involving, flexible referral pathways, suitable locations, adaptation of client engagement and service feedback processes) and, to a lesser extent, the nature and content of interventions (provision of culturally adapted therapy). Conclusions This study offers insights into key factors underpinning the successful national service implementation approach. Study findings highlight that concerted national attempts to enhance mainstream primary mental healthcare for Indigenous people are critically dependent on effective local agency- and provider-level strategies to optimise the integration, adaptation and broader utility of these services within local Indigenous community and healthcare service contexts. Despite the explicit provider focus, this study was limited by a lack of Indigenous stakeholder perspectives. Key study findings are of direct relevance to inform the future implementation and delivery of culturally appropriate primary mental healthcare programs for Indigenous populations in Australia and internationally.